TECHNOLOGICAL ASPECTS OF PINKING WHITE WINES, PREVENTION AND REMOVAL - Билько, Марина; Олейник, Алиса (SWorldJournal, 2020)
The effect of enzyme preparations on the appearance of pinking in white wine materials and auxiliary materials based on polyvinylpolypyralidone is investigated in the paper to reduce or prevent its occurrence.